Efficacy and safety of alfaxalone compared to propofol in canine refractory status epilepticus: a pilot study - Al Kafaji, Tania; Corda, Andrea; Charalambous, Marios; Murgia, Elsa; Tartari, Ilaria; Puci, Mariangela; Debidda, Pasquale; Gallucci, Antonella (Frontiers in Veterinary Science, 2024)
Abstract INTRODUCTION: Refractory status epilepticus (RSE) is defined as seizure activity that is minimally responsive to first- or second-line antiseizure medications. Constant rate infusion (CRI) intravenous propofol (PPF) is commonly used to treat RSE in dogs and cats. The antiseizure activity of alfaxalone (ALF) in RSE has been demonstrated in various experimental studies. This study compared the clinical efficacy and safety of intramuscular administration followed by CRI infusion of ALF with intravenous administration followed by CRI infusion of PPF to treat canine RSE. MATERIALS AND METHODS: This was a multicenter, prospective, randomized clinical trial of client-owned dogs referred for status epilepticus that did not respond to first- and second-line drugs. Animals with suspected or confirmed idiopathic or structural epilepsy were included. The dogs were randomly assigned to either the PPF or ALF treatment groups and each group received drug CRI infusions for six hours. Drug dosages were progressively reduced by 25% every hour from the third hour until suspension after six hours. Patients were classified as responders or non-responders based on the relapse of epileptic seizures during the twentyfour-hour therapy infusion or within twentyfour hours of drug suspension. Univariate statistical analyses were performed. RESULTS: Twenty dogs were enrolled in the study. Ten (10/20) dogs were randomly allocated to the PPF group and 10 (10/20) to the ALF group. Successful outcomes were obtained in six (6/10) patients in the PPF group and five (5//10) patients in the ALF group. Adverse effects were recorded in six (6/10) and three (3/10) animals in the PPF and ALF groups, respectively. No statistically significant differences in outcomes or the presence of adverse effects were observed between the groups. DISCUSSION: The results of this preliminary study suggest that ALF can be considered a valid and safe alternative to PPF for the treatment of RSE in dogs, with the additional advantage of intramuscular administration. However, caution should be exercised when using these drugs to provide airway and hemodynamic support.